Correlation of polyunsaturated fatty acids with the cold adaptation of Rhodotorula glutinis. Issue 11 (18th September 2015) - He, Jing; Yang, Zhaojie; Hu, Binbin; Ji, Xiuling; Wei, Yunlin; Lin, Lianbing; Zhang, Qi
Abstract This study aimed to investigate the correlation between the cold adaptation of Rhodotorula glutinis YM25079 and the membrane fluidity, content of polyunsaturated fatty acids and mRNA expression level of the Δ12‐desaturase gene. The optimum temperature for YM25079 growth was analysed first, then the composition changes of membrane lipid in YM25079 were detected by GC–MS and membrane fluidity was evaluated by 1‐anilinonaphthalene‐8‐sulphonate (ANS) fluorescence. Meanwhile, the encoding sequence of Δ12‐fatty acid desaturase in YM25079 was cloned and further transformed into Saccharomyces cerevisiae INVScl for functional analysis. The mRNA expression levels of Δ12‐fatty acid desaturase at 15°C and 25°C were analysed by real‐time PCR. YM25079 could grow at 5–30°C, with the optimum temperature of 15°C. The membrane fluidity of YM25079 was not significantly reduced when the culture temperature decreased from 25°C to 15°C, but the content of polyunsaturated fatty acids (PUFAs), including linoleic acid and α‐Linolenic acid increased significantly from 29.4% to 55.39%. Furthermore, a novel Δ12‐fatty acid desaturase gene YM25079RGD12 from YM25079 was successfully identified and characterized, and the mRNA transcription level of the Δ12‐desaturase gene was about five‐fold higher in YM25079 cells grown at 15°C than that at 25°C. These results suggests that the cold adaptation of Rhodotorula glutinis YM25079 might result from higher expression of genes, especially the Δ12‐fatty acid desaturase gene, during polyunsaturated fatty acids biosynthesis, which increased the content of PUFAs in the cell membrane and maintained the membrane fluidity at low temperature. Copyright © 2015 John Wiley & Sons, Ltd.